Phosphatized bacteria from the cretaceous phosphorites of Syria, Palmyra region - M. Alzammar; E. A. Zhegallo (Известия высших учебных заведений: Геология и разведка)
Background. Phosphatized bacteria of various shapes and numerous structures resulting from their vital activity have been found in the Late Cretaceous (Campanian) of Palmyra phosphorites deposits in Syria. Despite their great importance in the formation of phosphorite deposits, these bacteria have not been previously described in publications on Syrian phosphorites. This fact determines the relevance and originality of this study.   Aim. To identify and describe varieties of bacterial microfossils in Syrian phosphorites.   Materials and methods. The research material included the authors’ collection of phosphorites from the phosphate layers of the Alsharqiya quarry, thin sections for optical microscopy and samples for electron microscopic analysis. The photos of thin sections were obtained using a MIKMED-5 opticalmicroscope (Russia). A SEM analysis was conducted using a TESCAN VEGA-3, TESCAN VEGA-2 electron microscope (Czech Republic). A semi-quantitative elemental analysis of the sample composition was performed using an EVO-50 Zeiss electron microscope with an INCA Oxford 350 microanalyzer (UK). The samples were sputtered with gold.   Results. Five varieties of phosphatized bacteria, and five different structures formed as a result of their vital activity were identified. The internal structure of phosphate grains due to the activity of bacteria was established.   Conclusions. In addition to macrobionts (foraminifera, bivalves, bone remains, and other organic remains), a variety of bacteria were involved in the formation of Syrian phosphorites at the stage of sedimentation and diagenesis.